Integration and Differentiation as the Universal Scientific Categories and their Reflection in the Theory and Practice of Natural Science Education - V. A. Ignatova (Образование и наука)
The post-industrial society gives way to the qualitatively new formation of education, integrated at its every level: integration with science and production; cooperation of different educational establishments; succession of educational levels; cross-disciplinary and inter-disciplinary expertise development; choice of methods, technologies and organizational forms of education and upbringing, etc. The integration and differentiation in their didactic unity reflect the complexity and contradiction of educational process, either of them dominating in certain socio-economic conditions of the given historic period. The retrospective analysis of the above correlation regarding the natural science disciplines demonstrates the lack of theoretical and methodological bases for integration, and its accidental unsystematic character in educational processes. The main conclusion of the study is the need for the complex competence model to combine the ideas of integration and differentiation providing both the wide outlook and professional training. For overcoming the predominance of differentiated education, the author suggests adapting the concepts of post-non-classical science, and selection and structuring of educational information with the reference to the semantic universals of systematic synergetic approach. The research findings can be used in pedagogic research methodology, educational process design and modeling, its content, technology and organization.